SME adoption of digital banking in South Africa - Rathogwa, Belinda (My University, 2018)
Small and medium enterprises (SMEs) are an important customer base for banks as they offer great opportunity for growth in revenues and profit. Banks are focused on improving relationships and retaining their SME customers in defence against increasing competition. To this end, banks are investing in their digital banking channels with the objective of improving service quality to their SME customers, whilst lowering the cost of servicing those customers. It is not clear whether banks’ investment in digital banking channels is contributing to their objective of increasing customer satisfaction and retention. It is also not clear if SMEs derive the benefit of improved performance when they adopt digital banking. The purpose of this study was to establish the effect of digital banking adoption on the SME-bank relationship by evaluating its influence on customer satisfaction, loyalty and SME performance. Empirical data was collected in the form of an online survey which was administered to SME owner-managers who have gone through an incubation programme or have access to social media platforms for business purposes. Evidence suggests that banks are continuing to make significant investments in their digital channels. However, this does not necessarily result in more loyal or satisfied SME customers. Furthermore, SME performance does not improve as a result of adopting digital banking. Consequently, no evidence was found to show that digital banking adoption makes a significant contribution towards the maintenance of a long-term symbiotic relationship between SMEs and their banks. This study has corporate entrepreneurship implications for the banks as the findings will inform their innovation efforts and contribute to improving their service offerings to their SME customers.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management specialising in Entrepreneurship and New Venture Creation Johannesburg, February 2018
Keywords: Mobile commerce--South Africa; Technological innovations